The Effect of Brand Image, Brand Experience Through Brand Trust on Purchase Intention Brand Bwbyaz on Instagram - Isnubroto, Ristyuanke; Ridanasti, Erlita (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2025)
This study discusses the influence of brand image, brand experience through brand trust on purchase intention brand Bwbyaz on Instagram. This study uses a quantitative approach with nonprobability sampling techniques, purposive sampling method. Data collection was carried out by distributing questionnaires through social media. This study obtained a total of 166 respondents, but only 163 respondents whose data could be processed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method and the help of the SmartPLS application. The results of this study indicate that brand image and brand experience have a positive effect on brand trust. Furthermore, brand trust has a positive effect on purchase intention. Thus, the better the brand image and brand experience obtained by consumers from Instagram, the higher their level of trust in the Bwbyaz brand, which ultimately affects their increasing purchase intention. The results of the study can provide implications for the Bwbyaz brand, to always strengthen their brand image and provide a positive brand experience to build brand trust in order to encourage purchase intention in an effort to increase sales.